(untitled) (World Economics and Finance Bulletin, 2024)
The article presents a conceptual approach and a system of methods for identifying and quantifying the dynamic parameters of industrial production in the pre-crisis period and during periods of “waves” of coronavirus infection in the Republic of Uzbekistan. Based on the application of methods of multivariate statistical analysis and modeling, an assessment is made of the influence of these parameters on the recovery growth of industry in Uzbekistan. Integrated indicators of production growth in the post-crisis period have been generated, taking into account the features of both short-term fluctuations in production volumes and long-term trends in dynamics by type of industrial activity.